Optimizing the Role of the Ministry of Religious Affairs of NTB Province in Information and Communication Management for Nazhir Development and Empowerment of Waqf Assets - Suharti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the execution of his responsibilities outlined in article 11 of Law No. 41 of 2004 concerning Waqf, the Nazhir sought guidance from the Minister and the Indonesian Waqf Board. The primary objective of this study is to examine the program and enhance the effectiveness of the Regional Office of the Ministry of Religion in the NTB Province by utilizing information and communication management to support the Nazhir and bolster waqf assets on Lombok Island. Employing a qualitative-descriptive research approach, data collection involved methods such as observation, interviews, and documentation. The findings of the study suggest that the coaching initiative conducted by the Regional Office of the Ministry of Religious Affairs in the NTB Province, utilizing information and communication management to strengthen the capacity of Nazhir in enhancing waqf assets, has been structured in the form of various activities including training, counseling, workshops, orientation sessions, and similar endeavors. The guidance provided encompasses several aspects: 1) the enforcement of Law No. 41 of 2004 concerning Waqf; 2) enhancement of competencies for waqf managers (Nazhir); 3) the protection of waqf assets through legal means; 4) monitoring the implementation of waqf management; and 5) promoting community awareness about the significance of waqf assets within societal contexts. The coaching efforts conducted by the Regional Office of the Ministry of Religion in the NTB Province align with its institutional functions, serving as a regulator, facilitator, motivator, and provider of public services. However, due to financial limitations, the effectiveness of the coaching program is perceived as suboptimal, evident in the significant number of Nazhir who have yet to benefit from the guidance provided by the Regional Office of the Ministry of Religion in the NTB Province